2014
DOI: 10.13080/z-a.2014.101.012
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock effect on the performance of sweet cherry (Prunus avium L.) cv. ‘Vytėnų rožinė’

Abstract: In 1999-2009, at the Lithuanian Institute of Horticulture promising clonal rootstocks for sweet cherry (Prunus avium L.) cv. 'Vytėnų rožinė' were evaluated: Ž1 (Prunus cerasus L.), PN ('Vladimirskaya' × 'Polevka' × Padus mackii (Rupr.) Kom.), P3 and P7 (both -Cerapadus × (Prunus cerasus L. × P. avium L.)). Seedlings of a mahaleb cherry (Prunus mahaleb L.) served as a control. The trees on the rootstocks P3 and PN grew like the ones with P. mahaleb seedlings. At the end of the experiment their trunk diameter wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…To overcome this problem, the use of rootstocks that produce lower suckers is a valid alternative. The results agree with the Lanauskas et al (2012) results that reported that suckering of cherry rootstocks is influenced by the genotype.…”
Section: Effects Of Rootstock On the Growth Parameters Of Suckersupporting
confidence: 92%
See 1 more Smart Citation
“…To overcome this problem, the use of rootstocks that produce lower suckers is a valid alternative. The results agree with the Lanauskas et al (2012) results that reported that suckering of cherry rootstocks is influenced by the genotype.…”
Section: Effects Of Rootstock On the Growth Parameters Of Suckersupporting
confidence: 92%
“…In 'Khafr-e-Jahroom' scion, there was no significant difference between rootstocks and control related to sucker dry weight ( Figure 5). In previous studies, identified that sucker growth affected by rootstock (Vazifeshenas et al, 2009;Lanauskas et al, 2012). Our results showed that grafting combinations with 'Post Ghermaz-e-Aliaghai' rootstock had lower sucker weight which was in line with the findings of Lanauskas et al (2012) on cherry.…”
Section: Sucker Fresh and Dry Weightsupporting
confidence: 91%
“…These objectives have been accomplished by using size controlling and precocity rootstocks. Rootstocks used in sweet cherry culture directly affect the size and form of the tree, as well as precocity and yield (Fajt et al, 2009;Lanauskas et al, 2012). Moreover, they affect pruning, training system and labour decisions (Long, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Dwarf trees have a greater proportion of well illuminated canopy, low spray solution and higher labor efficiency. Rootstock influenced the tree growth (Cantin et al, 2010;Blazkova and Hlusickova, 2007), yield performance (Moreno et al, 2001), fruit quality (Whiting et al, 2005, Usenik et al, 2010, Lanauskas et al, 2012. Sansavini et al, (2001), reported, when 'Burlat 1', 'Durone Compatta di Vignola', 'Lapins' and 'Van' grafted on 20 clonal rootstock and planted in HDP system, bearing starts 4-5 years after planting and tree attained full bearing (10 kg tree -1 ) after 7-8 years.…”
Section: Introductionmentioning
confidence: 99%